Argumentative knowledge construction processes in social collaborative learning environment towards students’ higher order thinking skills - Ibrahim, Siti Nur Khadijah Aishah (2020)
In facing the challenges of the 21st century education, preparing learners towards higher order thinking skills (HOTS) is absolutely essential. To date, many researchers have highlighted the fact that learners are still dearth of HOTs, as dependency on examination-oriented rank and rote memorisation is inadequate to achieve this mission. At present, the implementation of collaborative problem-solving activities in the classroom as student-centred pedagogical practices appears to enhance learning performance effectively. Nevertheless, collaboration does not occur spontaneously, but demands a collaborative learning environment that naturally involves discussion with processes of evidence and argumentation. Argumentation refers to a claim supported by convincing evidence of extensive and comprehensive understanding of numerous aspects pertaining to an issue, in which knowledge is constructed, socially shared among peers, and benefiting individuals. Taking part in online discussions on social collaborative learning environment (SCLE) platform offers opportunities for learners to involve in argumentative debate. However, learners rarely formulate knowledgeable arguments or benefit individually from participating in online discussions. Therefore, the challenge lies in ensuring argumentative knowledge construction (AKC) process in SCLE, which can certainly enhance students’ thinking skills in line with HOTS. That being said, this study designed a SCLE using Edmodo to serve as an education tool by adopting the concept of a social network, as well as refining and making it appropriate for the classroom setting, so as to conduct three group discussion sessions for collaborative problem-solving tasks (CPT), with the aim of identifying how and what types of AKC process contribute to students’ HOTS. A group of undergraduate students from the Computer Science program had participated in this study (n=21). The mixed method research design, particularly the pre-experimental research design that involved type one group pre-test and post-test design, had been carried out. Data from the students’ performance test and CPT discussion in Edmodo group were collected and analysed using content analysis method to identify the AKC process and to evaluate the students’ HOTS performance. In order to further comprehend the thinking skills development and the AKC process in light of students’ HOTS, the interview technique was incorporated. The results retrieved from Wilcoxon signed rank test revealed statistically significant variance in the level of students’ HOTS in performance test (mean= 11.57; Z= -3.42, p= .001<.05). Next, the outcomes from Cohen (d= 0.81) exhibited the significant effect size of SCLE towards student performance in test. The triangulation results from the interview and the students’ discussion scripts for CPT highlighted six features of SCLE that contributed to the development of the students’ HOTS and AKC, namely: thinking space, stimulate HOTS, common environment, interactive learning, space for knowledge sharing, and instructor as facilitator. As for the AKC process, it was dominated by SOC2 dimension, which refers to questioning the learning partner or provoking a reaction from the learning partner. The study outcomes displayed that the AKC process promoted the students’ HOTS in SCLE through constructive interaction, intensive analysis, in-depth thinking, as well as persuasive and reasoning skills. Overall, based on the study findings, a framework of AKC process through SCLE has been developed as a guide to cultivate students’ HOTS and AKC process development.